2018
DOI: 10.1002/ange.201810222
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of the Campylobacter jejuni 81176 Strain Capsular Polysaccharide Repeating Unit Reveals the Absolute Configuration of its O‐Methyl Phosphoramidate Motif

Abstract: The O-methyl phosphoramidate (MeOPN) motif is anon-stoichiometric modification of capsular polysaccharides (CPS) in % 70 %ofall Campylobacter jejuni strains.Infections by C. jejuni lead to food-borne illnesses and the CPS they produce are key virulence factors.T he MeOPN phosphorus atom in these CPS is stereogenic and is found as as ingle stereoisomer.However,todate,the absolute stereochemistry at this atom has been undefined. We report the synthesis of the three repeating units found in C. jejuni 81-176 CPS;o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…272,273 The timing of methylation and phosphoryl transfer reactions to ultimately transfer MeOPN to the CPS remain to be delineated, although synthetic routes have demonstrated that the phosphorus in MeOPN exhibits an R-configuration. 274…”
Section: L-glutamine Phosphatementioning
confidence: 99%
“…272,273 The timing of methylation and phosphoryl transfer reactions to ultimately transfer MeOPN to the CPS remain to be delineated, although synthetic routes have demonstrated that the phosphorus in MeOPN exhibits an R-configuration. 274…”
Section: L-glutamine Phosphatementioning
confidence: 99%
“…Compound 34 is well poised for chain elongation to synthesize higher-order oligosaccharides and constitutes a protected repeating unit of S. aureus CP5. The conversion of azide to NHAc by using Zn/AcOH followed by treatment with Ac 2 O, MeOH, and Et 3 N, 56 purification on a silica gel column, and finally reductive removal of the remaining benzyl ethers and benzyloxycarbamate group by hydrogenolysis using H 2 (1 atm) and 20 wt % Pd(OH) 2 /C before passage through a Celite bed and lyophilization delivered target molecule 2 in 72% yield, over 3 steps. The 1 H NMR and 13 C NMR data of 2 correlated well with the earlier reported data.…”
Section: Regioselective Glycosylation Of Disaccharidementioning
confidence: 99%
“…Synthetic targets chemically obtained include repeating units (RUs) and related oligomers or analogs of CPSs (1-25) [10,12,[19][20][21][22][23][24][25][26][46][47][48][49][50][51][52][53][54][55][56][57][58][59], LPSs and LOSs [28][29][30][31][32][33][34][35][36][37][60][61][62][63][64][65][66][67][68][69][70][71][72], cell wall polysaccharides (50)(51)(52)(53)…”
Section: Chemically Synthesized Bacterial Surface Oligosaccharidesmentioning
confidence: 99%
“…The CPS oligosaccharides and analogs obtained (Figure 2A) include those from Hib (1) [19]; S. pneumoniae (Sp) serotypes ST1 (2) [20] ** , ST2 (3) [10], ST3 (4)(5) [21] ** , ST5 (6) [46], ST8 (7a-7d) [12] ** , ST11A (8) [22], and ST12F (9) [47]; group B Streptococcus (GBS) or Streptococcus agalactiae types Ia (10) [23], II (11) [24], VII (12) [25]; carbapenem-resistant Klebsiella pneumoniae (CR-Kp) (13) [26]; A. baumannii K47 (14) [48]; S. aureus types 5 (15) [49,61] and strain M (16) [50]; B. mallei (17) [51,52]; C. jejuni RM1221 (18) [53] ** and 81-176 (19) [54]; Bacteroides fragilis CPS PS A1 RU (20) [55]; Morganella morganii (21) [56]; C. bolteae (22) [27] ** , K. kingae KK01 (23) [57], C. psychrerythraea 34H (24) [58] and S. typhi (25) [59]. Among these, compounds 2, 20, 21, and 45 are repeating units of zwitterionic polysaccharides (ZPSs).…”
Section: Chemically Synthesized Bacterial Surface Oligosaccharidesmentioning
confidence: 99%